2021
DOI: 10.1210/clinem/dgab111
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Does not Affect the Prognoses of Differentiated Thyroid Cancer Patients With Lung Metastases

Abstract: Context Pregnancy-related hormones may stimulate thyroid cancer growth, but whether pregnancy affects the prognoses of patients with lung metastases from differentiated thyroid cancer (DTC-LM) after surgery and radioiodine therapy is unclear. Objective To assess the impact of pregnancy on DTC-LM through the comparison of prognoses between female patients with DTC-LM who did and did not become pregnant after surgery and radioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Previous studies have shown no differences in the survival, recurrence, or death between pregnancyassociated thyroid cancer and cancer in age-matched non-pregnant women [10] However, a more recent study reported that persistence/recurrence of DTC is signi cantly higher in pregnant patients, suggesting that pregnancy could exert a negative prognostic role in DTC patients, and more careful follow-up is needed in patients who are diagnosed with DTC during pregnancy or shortly thereafter [25]. Xi et al reported that the 10-year PFS and OS rates were 63.22% and 85.77%, respectively, in the pregnancy group (n = 37) versus 58.13% and 81.95%, respectively, in the non-pregnancy group (n = 87); thus, pregnancy does not affect the DTC prognoses in patients with lung metastasis [13]. In this study, the 10-year PFS rate (92.1%) was better than that in a previous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown no differences in the survival, recurrence, or death between pregnancyassociated thyroid cancer and cancer in age-matched non-pregnant women [10] However, a more recent study reported that persistence/recurrence of DTC is signi cantly higher in pregnant patients, suggesting that pregnancy could exert a negative prognostic role in DTC patients, and more careful follow-up is needed in patients who are diagnosed with DTC during pregnancy or shortly thereafter [25]. Xi et al reported that the 10-year PFS and OS rates were 63.22% and 85.77%, respectively, in the pregnancy group (n = 37) versus 58.13% and 81.95%, respectively, in the non-pregnancy group (n = 87); thus, pregnancy does not affect the DTC prognoses in patients with lung metastasis [13]. In this study, the 10-year PFS rate (92.1%) was better than that in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, there is no evidence showing that pregnancy worsens the prognosis of thyroid cancer [12,13]. Xi et al revealed that pregnancy does not affect the prognoses in DTC patients with lung metastasis [13].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Structural recurrence/progression was defined as appearance of new local/metastasis lesions, or 20% or more increase in size of a pre-pregnancy lesion 12,13 . Biochemical recurrence/progression was defined as 20% or more increase in serum thyroglobulin (Tg) from the pre-pregnancy level and/or consistent increase of 20% or more in serum anti-Tg antibodies 10,12 .…”
Section: Definitions Of Recurrence Risk Stratification and Response T...mentioning
confidence: 99%
“…Up to now, two Italian studies reported significantly higher risk of recurrence in patients who were diagnosed with DTC during pregnancy or soon after delivery 8,9 . As for DTC patients diagnosed and treated before pregnancy, a Chinese study claimed pregnancy has no impact on prognosis 10 . Discrepancy across studies may be attributed to the varied time of diagnosis (during pregnancy or prior to pregnancy), study design (single-group study or study with comparison group), or patients with different response to therapy status.…”
Section: Introductionmentioning
confidence: 99%